2023
DOI: 10.1097/iae.0000000000002987
|View full text |Cite
|
Sign up to set email alerts
|

Secondary in-the-bag Intraocular Lens Implantation in Aphakic Eyes After Vitrectomy and Silicone Oil Tamponade for Rhegmatogenous Retinal Detachment

Abstract: Purpose: To describe a novel technique for capsular bag reopening and secondary in-the-bag intraocular lens (IOL) implantation in aphakic eyes after vitreoretinal surgery and intraocular tamponade. Methods: We enrolled 14 eyes of 14 patients who underwent primary vitreoretinal surgery with silicone oil tamponade for rhegmatogenous retinal detachment between September 2018 and September 2019. The novel technique was used for capsular bag reopening and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…11 Recently, the blunt separation capsulotomy was reported by Wu et al, Li et al, and Liu et al, in which OVDs were injected into the peripheral space of the capsular bag and the adhesions between the anterior and posterior capsules were bluntly separated. [15][16][17] However, this method may not be suitable for pediatric aphakia with a severe proliferative membrane striding over the anterior and posterior capsulorhexis openings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Recently, the blunt separation capsulotomy was reported by Wu et al, Li et al, and Liu et al, in which OVDs were injected into the peripheral space of the capsular bag and the adhesions between the anterior and posterior capsules were bluntly separated. [15][16][17] However, this method may not be suitable for pediatric aphakia with a severe proliferative membrane striding over the anterior and posterior capsulorhexis openings.…”
Section: Discussionmentioning
confidence: 99%
“…14 The second category is the blunt separation capsulotomy, in which ophthalmic viscosurgical devices (OVDs) are used to bluntly separate the adhesion between the anterior and posterior capsules. [15][16][17] Nevertheless, this method may not be suitable for pediatric aphakia with a severe proliferative membrane striding over the anterior and posterior capsulorhexis openings.…”
mentioning
confidence: 99%
“…In recent research, Wu et al reported on reopening the fibrosed capsular bag via capsular forceps. 8 This method might be suitable for patient in favorable suspensorium statues, however, some cases with high myopia or trauma may suffer suspensorium weakness or dialysis, and their constricted bag cannot be forcibly opened with forceps. Our two-steps in-the-bag secondary IOL implantation involving two critical point: firstly, the "breaching point", we noticed that there is a relatively inattentive adhesion point in the constricted bag ring, with the point of a IOL hook, the anterior capsular could be readily lifted up to create a small gap in this point.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, several capsular bag reopening strategies were reported, 7 In Wu's work, constricted bag was reopened by capsular forceps and proliferation tissue removal. 8 Here,we introduce another novel method for capsular bag reopening ,with IOL hooks and sodium hyaluronate, we successfully detached constricted anteriorposterior capsular bag and the IOLs were implanted into the bag. This is a rather easy and low-risk method even in severe capsular adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al removed the fibroproliferative membranous material with capsulorhexis forceps or intraocular forceps. 12 Patients with severe fibrotic capsular bag have firm anterior-posterior capsular adhesions. For these cases, this method can cause zonular rupture and posterior capsule tears.…”
Section: Discussionmentioning
confidence: 99%